Addressing the inclusion imperative: an urban school district’s responses - DeMatthews, David Edward; Mawhinney, Hanne (Education Policy Analysis Archives, 2013)
Over the past forty years, schools across the United States have become more inclusive for students with disabilities. However, in many high-poverty urban school districts, a disproportionate number of minority children with disabilities are segregated from their non-disabled peers. This article presents findings from a qualitative case study of one urban school district implementing special education-related inclusion reform over the course of four years. The district had a history of segregating students and numerous compliance issues with special education mandates; however, the arrival of a new superintendent brought new hopes for change. The authors argue that existing research regarding inclusion has typically ignored the policy implementation processes employed by school districts in establishing more inclusive schools and improved special education programs. This article provides a case description of a district’s special education inclusion policy implementation process, the challenges district administrators were confronted with, and the positive and negative outcomes of the district’s policies. The findings inform next-generation policy initiatives and future lines of inquiry.